Tan Particle Motion

Calculus Level 4

A particle undergoes acceleration from rest according to the formula a = tan t a=\tan t , where a = d 2 x d t 2 a=\dfrac{d^2x}{dt^2} is the acceleration of the particle at time t t .

Find the distance traveled by the particle in π 2 \frac{\pi}{2} seconds. The result can be written in the form a π ln b a\pi\ln b , where a a is rational and b b is prime. Give your answer as a b ab .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 17, 2018

a = tan t v = tan t d t where v = d x d t is the velocity. = sin t cos t d t = d cos t cos t = ln ( cos t ) + C where C is the constant of integration. v ( 0 ) = ln ( cos 0 ) + C = 0 C = 0 v = ln ( cos t ) \begin{aligned} a & = \tan t \\ \implies \color{#3D99F6} v & = \int \tan t \ dt & \small \color{#3D99F6} \text{where } v = \frac {dx}{dt} \text{ is the velocity.} \\ & = \int \frac {\sin t}{\cos t} dt \\ & = - \int \frac {d \cos t}{\cos t} \\ & = - \ln (\cos t) + \color{#3D99F6} C & \small \color{#3D99F6} \text{where }C \text{ is the constant of integration.} \\ \because v(0) & = - \ln (\cos 0) + C = 0 &\small \color{#3D99F6} \implies C = 0 \\ \implies v & = - \ln (\cos t) \end{aligned}

Therefore, the distance traveled after π 2 \frac \pi 2 s:

x ( π 2 ) = 0 π 2 ln ( cos t ) d t Using a b f ( x ) d x = a b f ( a + b x ) d x = 1 2 0 π 2 ( ln ( cos t ) + ln ( sin t ) ) d t = 1 2 0 π 2 ln ( sin t cos t ) d t = 1 2 0 π 2 ln ( 1 2 sin ( 2 t ) ) d t = 1 2 0 π 2 ( ln ( sin ( 2 t ) ) ln 2 ) d t Let u = 2 t d u = 2 d t = 1 4 0 π ln ( sin u ) d u + 1 2 0 π 2 ln 2 d t Since sin u is symmetrical about π 2 = 1 2 0 π 2 ln ( sin u ) d u + t ln 2 2 0 π 2 Using a b f ( x ) d x = a b f ( a + b x ) d x = 1 2 0 π 2 ln ( cos u ) d u + π ln 2 4 = 1 2 x ( π 2 ) + π ln 2 4 = π ln 2 2 \begin{aligned} x \left(\frac \pi 2\right) & = - \int_0^\frac \pi 2 \ln (\cos t) \ dt & \small \color{#3D99F6} \text{Using }\int_a^b f(x) \ dx = \int_a^b f(a+b-x) \ dx \\ & = - \frac 12 \int_0^\frac \pi 2 (\ln (\cos t) + \ln (\sin t)) \ dt \\ & = - \frac 12 \int_0^\frac \pi 2 \ln (\sin t\cos t) \ dt \\ & = - \frac 12 \int_0^\frac \pi 2 \ln \left(\frac 12 \sin (2t)\right) \ dt \\ & = - \frac 12 \int_0^\frac \pi 2 (\ln (\sin ({\color{#3D99F6}2t})) - \ln 2 ) \ dt & \small \color{#3D99F6} \text{Let }u = 2t \implies du = 2\ dt \\ & = - {\color{#3D99F6}\frac 14 \int_0^\pi \ln (\sin u)\ du} + \frac 12 \int_0^\frac \pi 2 \ln 2 \ dt & \small \color{#3D99F6} \text{Since }\sin u \text{ is symmetrical about }\frac \pi 2 \\ & = - {\color{#3D99F6} \frac 12 \int_0^\frac \pi 2 \ln (\sin u)\ du} + \frac {t \ln 2}2 \ \bigg|_0^\frac \pi 2 & \small \color{#3D99F6} \text{Using }\int_a^b f(x) \ dx = \int_a^b f(a+b-x) \ dx \\ & = - {\color{#3D99F6} \frac 12 \int_0^\frac \pi 2 \ln (\cos u)\ du} + \frac {\pi \ln 2}4 \\ & = \frac 12 x \left(\frac \pi 2\right) + \frac {\pi \ln 2}4 \\ & = \frac {\pi \ln 2}2 \end{aligned}

Therefore, a b = 1 2 × 2 = 1 ab = \frac 12 \times 2 = \boxed{1} .

Mark Hennings
Mar 16, 2018

The velocity is v = ln ( sec t ) v = \ln(\sec t) , and so the distance travelled is 0 1 2 π ln ( sec t ) d t = J \int_0^{\frac12\pi} \ln(\sec t)\,dt \; = \; -J where J = 0 1 2 π cos t d t = 0 1 2 π sin t d t J \; = \; \int_0^{\frac12\pi} \cos t\,dt \; = \; \int_0^{\frac12\pi} \sin t \,dt and hence 2 J = 0 1 2 π sin t cos t d t = 0 1 2 π 1 2 sin 2 t d t = 0 1 2 π sin 2 t d t 1 2 π ln 2 = 1 2 0 π sin t d t 1 2 π ln 2 = 1 2 × 2 0 1 2 π sin t d t 1 2 π ln 2 = J 1 2 π ln 2 \begin{aligned} 2J & = \; \int_0^{\frac12\pi} \sin t \cos t\,dt \; = \; \int_0^{\frac12\pi} \tfrac12\sin 2t\,dt \; = \; \int_0^{\frac12\pi} \sin2t\,dt - \tfrac12\pi\ln2 \\ & = \; \tfrac12 \int_0^{\pi}\sin t\,dt - \tfrac12\pi\ln2 \; = \; \tfrac12 \times 2 \int_0^{\frac12\pi} \sin t\,dt - \tfrac12\pi \ln2 \; = \; J - \tfrac12\pi\ln2 \end{aligned} so that J = 1 2 π ln 2 J = -\tfrac12\pi\ln2 , making the distance travelled 1 2 π ln 2 \tfrac12\pi\ln2 , and so the answer is 1 2 × 2 = 1 \tfrac12 \times 2 = \boxed{1} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...